Technology for Anticorrosive Protection of Steel Structures by Coatings Based on Rapid-Setting Bitumen-Latex Emulsion - Nykyforchyn, H.M.; Chervatyuk, V.A.; Marukha, V.I.; Slobodyan, Z.V.; Kushnir, І.M.; Stechnovych, L.V. (Science and Innovation, 2024)
Mix formulas for rapid-setting bitumen-latex emulsions and coatings based on them have been designed; in-laboratory tests of their physical, chemical, and anticorrosive properties have been carried out. The technology for anticorrosive protection and the technical documents for preparing the aqueous bitumen-latex emulsion have been designed; a plant has been mounted and a pilot batch of rapid-setting emulsion has been produced. The technology has applied to pipelines in the oil and gas industry.